Análise do perfil de segurança do uso de tacrolimo em exposição reduzida e everolimo ou micofenolato de sódio em receptores de transplante renal - Miranda, Tamiris Abait [UNIFESP] (2020)
Methodology: A sub - analysis of safety data not yet tested in the original study was performed. Adverse event data were classified according to Common Terminology Criteria for Adverse Events (CTCAE / meDRa) version 4.0 according to manual hierarchy levels and laboratory parameters were classified according to CTCAE scores according to scale from 1 to 5. being 1 (mild), 2 (Moderate), 3 (severe or clinically significant), 4 (life threatening) and 5 (death). Categorical variables were presented as absolute and relative frequency, and for comparison between groups, the chi-square test was performed, continuous variables were summarized by mean and standard deviation, and comparisons between groups at follow-up were performed using the mixed linear normal modal with a random effect of the individual, for the variables that violated the assumption of normality, comparisons between groups were performed using the gamma-distributed GEE model. Results: A total of 2741 adverse events (AEs) and 344 serious adverse events (SAEs) were observed, and approximately 100% of patients had at least 01 AE. When analyzing adverse events without seriousness criteria, between the r-ATG/EVR and BAS/EVR groups, a statistical difference was observed in the events related to gastrointestinal disorders, infections, nervous system disorders and skin. Between r-ATG/EVR and BAS/MPS groups, a statistical difference was observed in events related to gastrointestinal disorders, events related to procedural complications, metabolism, skin and general disorders. Between the BAS/EVR and BAS/MPS groups, a statistical difference was observed in the events related to infections and metabolism and general disorders. For serious adverse events only events related to gastrointestinal, renal and urinary disorders, besides infections had some statistical difference between the three groups. For laboratory analysis, 35% of the analyzes showed some alteration, from mild, moderate, severe and life threatening. Conclusion: The present safety analysis showed that adverse events and laboratory changes were in agreement with the literature for the three immunosuppressive regimens. Also, although well-established in its efficacy, the MPS regimen is associated with significant adverse events that result in worse renal transplant outcome as CMV infection, demonstrated in the main study, leading to intolerability of MPS use and drug changing, which may increase the risk of acute rejection.